PENINGKATAN MUTU PEMBELAJARAN QUR'AN MELALUI SOSIALISASI METODE TAHFIDZ DAN PELAKSANAAN HALAQAH DI TAMAN PENDIDIKAN AL-QUR’AN - Arqam, M Rukhul; Indri Karadona, Rosika; Puspita Sari, Arni (CV. Kalimasada Group, 2025)
Qur’anic learning in Taman Pendidikan Al-Qur’an (TPA) plays a vital role in instilling Islamic values from an early age. However, challenges such as the lack of systematic teaching methods, limited parental involvement, and weak memorization evaluation systems continue to hinder learning quality. This community service program aims to improve the quality of Qur’an education through three main approaches: socialization of the tahfidz method to parents, training and mentoring of halaqah for teachers, and structured implementation and evaluation of halaqah with students. The method applied is Participatory Action Research (PAR), which emphasizes active involvement of all stakeholders. The results show significant improvements in parental understanding and participation, teachers’ competence in managing halaqah, as well as students’ motivation and memorization achievements. This program demonstrates that the structured and collaborative application of the tahfidz method can be an effective strategy to build a more qualified and sustainable Qur’anic learning system.